13VALIDITY OF LADDER SNAKE MEDIA TO TRAIN COOPERATION AND ENHANCE LEARNING OUTCOME OF STUDENTS ON DIGESTIVE SYSTEM - Nanik Indra Rukmana; Isnawati Isnawati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
Learning plays a role in determining students learning mastery. One of the element in the mastery of learning is cooperation. Cooperation is very closely related to the survival of human life. Learning also make positive contribution to better improvement. One of the improvement that can be measured is learning outcome. The learning outcome is measurement tool to know the accuracy of learning strategy and as the reflection to learning that has been done. Digestive system is one of the material that has many provision. This material commonly uses powerpoint slide, lecture and discussion. This does not suit with the idea of 2013 Curriculum. In the 2013 Curriculum changes the learning pattern to be student-centered. The alternative solution of this problem is using variation in learning. One of the variation that can be done is learning media. Learning media that can assess the cooperation, learning outcome and fits the 2013 curriculum is digestive system ladder snake media. The aim of this study was to produce feasible digestive system snake ladder based on its validity. The procedure of this result used ASSURE model (Analyzing learners, State media objectives, Selecting method and media materials, Utilizing materials, Requiring learners perfomance, and Evaluating/Revising). The limited test was carried out to 30 students of Grade XI in SMA Negeri 1 Bojonegoro. Validity of media was determined based on the validation result by the media and material experts. The validity score was 3. 95 in very valid category. Based on that validity score, the developed digestive system ladder snake media was stated as feasible. Keywords : Validity, Ladder Snake Media, Learning Outcome, Cooperation, Digestive System.